A semiparametric factor model for electricity forward curve dynamics - Szymon Borak; Rafał Weron (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
In this paper we introduce the dynamic semiparametric factor model (DSFM) for electricity forward curves. The biggest advantage of our approach is that it not only leads to smooth, seasonal forward curves extracted from exchange traded futures and forward electricity contracts, but also to a parsimonious factor representation of the curve. Using closing prices from the Nordic power market Nord Pool we provide empirical evidence that the DSFM is an efficient tool for approximating forward curve dynamics.
Keywords: C51; G13; Q40; 330; Power market; forward electricity curve; dynamic semiparametric factor model; Stromtarif; Rohstoff-Futures; Faktorenanalyse; Nichtparametrisches Verfahren; Nordeuropa